The Challenges of Adoption of Eco Single Currency among ECOWAS Member-States - Anele, Livinus; Anuga, Joseph (African Journal of Politics and Administrative Studies, 2024)
The Economic Community of West African States, ECOWAS, had an agreement to adopt the Eco as its single currency for the fifteen member-states of the West African Sub-regional organization. This major objective has failed to materialize after a long period of time. This paper, therefore seeks to highlight the major challenges confronting the Eco currency project. Data were collected from secondary sources, using content analysis. The paper of discusses the challenges facing the proposed Eco single currency in West Africa, discusses the theoretical framework of monetary integration using Mundell’s factors of Mobility Theory and Mundell’s Optimum Currency Area Theory applied. Based on the findings, Some of the challenges facing the proposed Eco currency in ECOWAS include lack of political will, influence of France on its former territories in West Africa, membership of multiple regional blocs by member states of ECOWAS and fear of domination of the smaller states in the bigger ones. Other challenges include; security and political challenges, inadequate legal instruments to enforce treaty obligations, inadequate modern infrastructure among others. To make this proposed Eco currency a success, the paper suggests that West Africa Monetary Zone member states must take concrete action by showing political will towards the creation of Eco currency area in West Africa. There should be clearly spelt out benefits and costs accruing to each member state in the proposed Eco community currency area. All member states of ECOWAS must be treated as equal partners.
Keywords: Adoption; Anglophone-Francophone; Development; ECOWAS; Eco single currency

From red tape to red carpet: the Unidroit Cape Town Convention and MAC Protocol’s Adventure in Africa - Otabor-Olubor, Iyare (Uniform Law Review, 2024)
This article examines the implementation of the Mining, Agricultural and Construction (MAC) Equipment Protocol under the Cape Town Convention in Africa, focusing on enhancing economic growth and sustainable development through improved access to financing for high-value mobile equipment. Africa’s economic development is significantly hindered by inadequate infrastructure, which escalates transaction costs and limits access to international markets. Investment in modern infrastructure, particularly in the mining, agricultural, and construction sectors, is typically expensive for many businesses in the African region. The MAC Protocol aims to address these challenges by providing a uniform legal framework that supports the financing of MAC equipment. The Convention and the MAC Protocol facilitate access to affordable capital and reduce risks for financiers who take international interests in MAC equipment, promoting economic activities in Africa. The article highlights the legal protections offered by the MAC Protocol, ensuring rights against third-party claims and enhancing the enforceability of international interests. The adoption of the MAC Protocol by African States could significantly impact their ability to meet the United Nations Sustainable Development Goals by making modern, cost-efficient equipment more accessible, thus boosting productivity and economic diversification. The article advocates for adopting the MAC Protocol, emphasizing its potential to enhance foreign investment in the mining, agriculture, and construction sectors, stimulating economic development in Africa. This strategic move will propel African countries towards greater economic resilience and integration into the global economy. The article also critically analyses and illustrates the several declaration mechanisms available to countries adopting the MAC Protocol, accompanied by a guidance note to sensitize lawmakers when signing and/or ratifying or acceding to the Cape Town Convention and the MAC Protocol.

The efficient enforcement challenge of secured transactions law reforms in civil law systems: self-help repossession, strict foreclosure, and other methods for the acceleration of enforcement of security interests - Tajti (Thaythy), Tibor (Uniform Law Review, 2024)
Although the forging of an efficient system for enforcement of security interest is one of the central expectations of secured transaction law reforms in civil law systems, the results hardly give reason for satisfaction. As the reforms tend to be supported and influenced by various international organizations’ projects (especially the World Bank, the European Bank for Reconstruction and Development, the International Institute for the Unification of Private Law, and the United Nations Commission on International Trade Law), most out-of-court methods of enforcement of security interests have played a central role. Yet due to civil law’s general hostility towards self-help as such, either the introduction of the concept has been rejected or the local limited-reach kin have been merely ‘paper tigers’. Similarly, although security interests on several types of collateral (accounts, investment property) or on the workhorse of the English financial system—the floating charge—have also been enforced extrajudicially (save the exceptions), little attention has been attributed to these enforcement modalities. The same applies to strict foreclosure in civil law systems still being prohibited, or restricted, and thus rarely resorted to, due to the inherited hostility towards the doctrine of lex commissoria. Rethinking local laws on preliminary and temporary court orders to match them with such globally known ex parte preliminary measures as the English Mareva Injunction or the French Saisie Conservatoire, which allow creditors to swiftly freeze debtors’ assets and thus substitute self-help repossession, has also been given short shrift. The enforcement segment, consequently, remains the Achilles’ heel of secured transaction law reforms in civil law systems. This article desires to contribute to reform literature by addressing these deficiencies and by offering tested, fully or partially fitting, functional equivalents of self-help repossession.

States and Regional International Organizations - Zouapet, Apollin Koagne (International Organizations Law Review, 2024)
Beyond the thorny, even insoluble question of the definition of a region and the definition of the criteria that should make it possible to apprehend the polymorphism of rio s, the raison d’être of these organizations, their mode of operation and their activities are at the heart of the debate on “international governance”. For many authors, the advent of RIO s has often been seen as a challenge to the state monopoly in the international legal order and a redefinition of the relationship between these particular organizations and states. It is this relational dynamic between the States and the RIO s that this contribution aims to describe and analyse. The aim is to examine the originality and specificity of the relationship between the RIO s and the States, compared to the latter’s relationship with the ‘classic/universal’ ios, which would reveal something about the very nature of regional organizations.
PDF: https://brill.com/downloadpdf/view/journals/iolr/21/1/article-p147_008.pdf
Keywords: Cooperation; Instrumentalism; Integration; Regionalism; Supranationalism; Universalism

The Impact of the United Nations Human Rights Treaties on the Domestic Level: Twenty Years On - Heyns, Christof; Viljoen, Frans Jacobus; Murray, Rachel (Brill, 2024)
This collection of chapters tracks and explains the impact of the nine core United Nations human rights treaties in 20 selected countries, four from each of the five UN regions. Researchers based in each of these countries were responsible for the chapters, in which they assess the influence of the treaties and treaty body recommendations on legislation, policies, court decisions and practices. By covering the 20 years between July 1999 and June 2019, this book updates a study done 20 years ago.
PDF: https://brill.com/downloadpdf/edcollbook-oa/title/38945.pdf
Keywords: Comparative Social Sciences; Human Rights; Human Rights and Humanitarian Law; Humanitarian Law; International Law; International Law: Regional Perspectives

The Impact of the United Nations Human Rights Treaties on the Domestic Level in Senegal - Kane, Ibrahima (The Impact of the United Nations Human Rights Treaties on the Domestic Level: Twenty Years On, 2024)
"Chapter 16 The Impact of the United Nations Human Rights Treaties on the Domestic Level in Senegal" published on 09 Feb 2024 by Brill | Nijhoff.
Section: The Impact of the United Nations Human Rights Treaties on the Domestic Level: Twenty Years On
Keywords: Comparative Social Sciences; Human Rights; Human Rights and Humanitarian Law; Humanitarian Law; International Law; International Law: Regional Perspectives; Social Sciences

Uniform Law: Legal Responses to Globalisation - Basedow, Jürgen; Max-Planck-Institut für Ausländisches und Internationales Privatrecht (Hamburg, Germany) (Mohr Siebeck, 2024)
International conference proceedings
Keywords: COMMERCIAL LAW; Economic Analysis; PRIVATE INTERNATIONAL LAW; Uniform law

Measuring the Effects of Post-Convention Activities at the HCCH - Zhang, Ke (McGill University, 2024)
https://escholarship.mcgill.ca/concern/theses/cn69m944k
Keywords: HCCH; Hague Conference on Private International Law